Pathogenesis of Middle East respiratory syndrome coronavirus. Issue 2 (January 2015) - van den Brand, Judith MA; Smits, Saskia L; Haagmans, Bart L
Abstract Human coronaviruses (CoVs) mostly cause a common cold that is mild and self‐limiting. Zoonotic transmission of CoVs such as the recently identified Middle East respiratory syndrome (MERS)‐CoV and severe acute respiratory syndrome (SARS)‐CoV, on the other hand, may be associated with severe lower respiratory tract infection. This article reviews the clinical and pathological data available on MERS and compares it to SARS. Most importantly, chest radiographs and imaging results of patients with MERS show features that resemble the findings of organizing pneumonia, different from the lesions in SARS patients, which show fibrocellular intra‐alveolar organization with a bronchiolitis obliterans organizing pneumonia‐like pattern. These findings are in line with differences in the induction of cytopathological changes, induction of host gene responses and sensitivity to the antiviral effect of interferons in vitro when comparing both MERS‐CoV and SARS‐CoV. The challenge will be to translate these findings into an integrated picture of MERS pathogenesis in humans and to develop intervention strategies that will eventually allow the effective control of this newly emerging infectious disease. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.